1979
DOI: 10.1111/j.1365-2133.1979.tb05579.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 8-methoxypsoralen plus UVA (PUVA) on lymphocyte transformation and T cells in psoriatic patients

Abstract: The peripheral blood lympochytes of the psoriatic patients studied initially showed a normal response to phytohaemagglutinin (PHA) and to purified protein derivative of tuberculin (PPD) in a microculture using whole blood, but a lower than normal response to a high concentration of concanavalin A (Con A). The initial level of E-rosette-forming T cells in psoriatic patients (51 3%) was significantly lower than that in healthy controls (66 7/,,).A single exposure to 8-methoxypsoralen (8-MOP) and UVA light (PUVA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1979
1979
1996
1996

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Many of the nonlethal immune-modulating effects, however, should be short-lived, suggesting that long-term benefits (months to years) derived from PUVA treatment of diseases such as psoriasis and CTCL m a y be based, instead, in the ability of P U V A to delete activated T-cell clones, which are preferentially located in the skin (24). In psoriasis, PUVA treatment depletes >90% of T-lymphocytes infiltrating cutaneous lesions (3), but comparatively small effects are produced o n circulating T-lymphocytes (25)(26)(27). Hence the ability of P U V A to deplete o r eliminate specific intracutaneous T-cell clones by direct cytotoxic actions may underlie its ability t o induce disease remissions in diseases such as psoriasis and CTCL.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the nonlethal immune-modulating effects, however, should be short-lived, suggesting that long-term benefits (months to years) derived from PUVA treatment of diseases such as psoriasis and CTCL m a y be based, instead, in the ability of P U V A to delete activated T-cell clones, which are preferentially located in the skin (24). In psoriasis, PUVA treatment depletes >90% of T-lymphocytes infiltrating cutaneous lesions (3), but comparatively small effects are produced o n circulating T-lymphocytes (25)(26)(27). Hence the ability of P U V A to deplete o r eliminate specific intracutaneous T-cell clones by direct cytotoxic actions may underlie its ability t o induce disease remissions in diseases such as psoriasis and CTCL.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of PUVA therapy on lymphocyte sub-populations has also been examined by several groups with a similar variation in the results. Fraki et al (1979) found that the proportion of circulating E-rosette-forming cells rose in a group of patients with psoriasis during a 12-week course of PUVA therapy. The mean result for the twelve patients was 51-3% before therapy and 62-8% after therapy, as compared to 667% in a healthy control group.…”
Section: Resultsmentioning
confidence: 96%
“…The results obtained in these studies have varied. The response of lymphocytes to stimulation by PHA was found not to alter during the course of PUVA therapy in three studies (Ortonne et al, 1978;Wassilew, 1978;Fraki, Eskola & Hopsu-Havu, 1979). Blood samples were obtained either immediately after or immediately before exposures to PUVA; in the latter case it is not possible to be certain of the time lapse after the last exposure to PUVA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the relevance of these experimental studies for the situation obtaining in PUVA treated psoriatic skin remains unclear. Although Kraemer & Weinstein (1977) reported a decrease in DNA synthesis in non-stimulated lymphocytes from PUVA treated patients and several authors have found a decrease in mitogen response in lymphocytes taken at various times during a course of PUVA therapy (Lischka et al, 1977;Morison et al, 1979b;Friedmann & Rogers, 1980), others have failed to detect any change (Ortonne et al, 1978;Wassilew, 1978;Fraki, Eskola & Hopsu-Havu, 1979;Harper et al, 1979), and also there is no increase in sister chromatid exchange rate in circulating blood cells from patients undergoing PUVA therapy (Wolff-Schreiner et al, 1977;Faed et al, 1980).…”
Section: Discussionmentioning
confidence: 99%